2017
DOI: 10.1371/journal.pone.0182379
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of long-term outcomes of enzyme replacement therapy in Fabry disease: Analysis of prognostic factors

Abstract: Despite enzyme replacement therapy, disease progression is observed in patients with Fabry disease. Identification of factors that predict disease progression is needed to refine guidelines on initiation and cessation of enzyme replacement therapy. To study the association of potential biochemical and clinical prognostic factors with the disease course (clinical events, progression of cardiac and renal disease) we retrospectively evaluated 293 treated patients from three international centers of excellence. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 44 publications
5
62
0
4
Order By: Relevance
“…ERT with intravenous administration of recombinant human a-D-galactosidase (agalsidase beta, Fabrazyme® or agalsidase alpha, Replagal®) reduces the levels of Gb3 and lyso-Gb3 in some tissues of Fabry patients, but its clinical efficacy is still limited. [5][6][7]43 The limited enzyme stability in plasma is a major drawback, and it is for this reason that enzyme active site binders that stabilize recombinant enzyme in circulation are pursuedwith Gal-DNJ 8 (Migalastat®) currently in use in the clinic as the benchmark. Here we report the design and synthesis of the rst-in-class conformational glycosidase inhibitor and agal A stabilizing agent, a-cyclosulfamidate 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERT with intravenous administration of recombinant human a-D-galactosidase (agalsidase beta, Fabrazyme® or agalsidase alpha, Replagal®) reduces the levels of Gb3 and lyso-Gb3 in some tissues of Fabry patients, but its clinical efficacy is still limited. [5][6][7]43 The limited enzyme stability in plasma is a major drawback, and it is for this reason that enzyme active site binders that stabilize recombinant enzyme in circulation are pursuedwith Gal-DNJ 8 (Migalastat®) currently in use in the clinic as the benchmark. Here we report the design and synthesis of the rst-in-class conformational glycosidase inhibitor and agal A stabilizing agent, a-cyclosulfamidate 4.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 C 1 minimum of the substrate extends towards the TS-like 4 H 3 conformation, indicating that cyclosulfate 2 in a 4 H 3 conformation could be transiently populated on-enzyme, favoring the nucleophilic attack and formation of a glycosyl-enzyme adduct. The FELs of 3-5 show that substitution of the cyclic sulfate trap by cyclic sulfamidates (3 and 4) or sulfamide (5) does not signicantly affect the conformational preferences. The local B 2,5 minimum in 4 is more pronounced, probably due to a hydrogen bond between the 2-OH and one cyclosulfamidate oxygen (Fig.…”
Section: Conformationmentioning
confidence: 99%
“…Recently, we have described the absolute slopes for eGFR, LVMI of patients on treatment stratified for phenotype and sex which might be used as benchmark for future studies. 30 This study also emphasises the fact that in some patients there is irreversible damage to organs such as the kidneys, which will not be reversed. It was shown that in patients with advanced kidney disease, the risk…”
Section: Therapeuticsmentioning
confidence: 87%
“…Some work on developing such starting and stopping criteria has been done . It is easy to portray such efforts as being about restricting treatment and saving costs, but that narrative, which does not come solely from the pharmaceutical industry, should be resisted.…”
Section: Discussionmentioning
confidence: 99%